The Effect Of Different Postharvest Treatments On The Changes In The Physico-Chemical Characteristics And Manifestation Of Chilling Injury Of Pisang Mas (Musasapientumvar. Mas) During Storage At Low Temperature - Febrimeli, Dwi (2000)
Preliminary studies on the effect of storage temperature and heat treatments on the physical characteristics were carried out on Pisang Mas (Musa sapientum var. Mas). Temperature 1 4± 1°C; 65-83%RH was the most suitable storage temperature for Pisang Mas with respect to peel colour score and texture as compared to temperature 1 2°C and 1 5°C. In contrast to peel colour score and pulp: peel ratio, fruit texture decreased significantly (P<0.05) during storage. Heat treatments (hot air at 3 0, 40 and 50°C for 3 and 6 hours or dipping in hot water at 50°C for 2 minutes) reduced the manifestation of physical symptoms of chilling injury and extended the storage life of Pisang Mas by 2 weeks as compared to the control fruits. Effect of different postharvest heat treatments prior to low temperature storage were studied to reduce the manifestation of chilling injury of Pisang Mas during storage at low temperature and when held at ambient conditions thereafter. During low temperaturestorage, untreated fruit were shown to have a significantly (P<0.05) higher manifestation of chilling injury. Fruits exposed to 30°C hot air for 3 hours could significantly (P<0.05) reduced chilling injury symptoms in Pisang Mas. Different postharvest heat treatments could not significantly extend the shelf life of Pisang Mas as compared to control. Peel colour, pulp colour, pulp: peel ratio, total soluble solids (TSS), titratable acidity (T A), TSS : TA ratio, total sugar, fructose, glucose and sucrose of fruit increased significantly (p<0.05) during storage, in contrast to fruit firmness, pH, ascorbic acid (AA), tannin and starch contents. Chilling injury was also evident in all treated fruit after 2 and 4 weeks at low temperature storage followed by storage at ambient conditions. However, fruits kept for 4 week at low temperature (L TS) had a lesser extent of chilling injury as compared to fruit kept for 2 weeks at LTS . Fruits kept for 2 and 4 weeks under LTS had a shelf life of 9 and 6 days respectively. The TSS, TSS: TA ratio, pH and AA of fruit increased significantly (p<0.05) for all treated fruits and control during storage. The firmness and starch content decreased significantly (P<0.05). On the other hand, TA and tannin content were found to fluctuate during storage. Different concentrations of methyl jasmonate in reducing chilling injury were studied in Pisang Mas. Concentration higher than 1 00 .. were found not to be sigl}ificantly different in reducing symptoms of chilling injury. Although methyl jasmonate did not affect peel colour, nevertheless pulp colour was slightly affected. The TSS and pulp to peel ratio increased significantly (P<0.05) during storage. However, firmness, AA, TA, pH, tannin, starch and pectin contents of fruit from all treatments were found to be inconsistent during storage.